Correlation analysis between surface electromyography and continuous-wave near-infrared spectroscopy parameters during isometric exercise to volitional fatigue - ÇOTUK, HASAN BİROL (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2014)
In this study, the process of muscular fatigue was examined using surface electromyography (sEMG) and continuous-wave near-infrared spectroscopy (cw-NIRS) simultaneously during an isometric hand grip exercise at 50% and 75% of the maximal voluntary contraction (MVC), sustained until volitional fatigue. The mean frequency of the sEMG decreased during the whole exercise, whereas the root mean square had a tendency to increase. Oxyhemoglobin/deoxyhemoglobin concentration changes computed with cw-NIRS were found to exhibit a fast linear decrease/increase in the first 10-20 s of the exercise, the so-called fast phase, followed by a plateau-like slow phase. The change rates were higher at 75% MVC for both the sEMG and cw-NIRS parameters. Significant correlations were found, especially at 50% MVC, between the sEMG parameters computed for the whole exercise and cw-NIRS parameters computed from the early region of the exercise, i.e. infection duration and amplitude changes to the inflection point. The findings emphasize the potential of cw-NIRS for muscle studies.
Keywords: Fatigue; oxygenation; near-infrared spectroscopy; surface electromyography; isometric exercise; FLEXOR DIGITORUM SUPERFICIALIS; HUMAN SKELETAL-MUSCLE; MYOELECTRIC ACTIVITY; TISSUE OXYGENATION; LONG-DURATION; EMG; CONTRACTIONS; PHYSIOLOGY; THRESHOLD; FOREARM